Ilocano language patterns of address, greeting and leave-taking - Guerrero, Nieves (Jamias) 1924- (s.n.], 1972)
Through a descriptive survey of how Ilocanos address and greet each other and how they take their leave, this study attempted to verify the validity of the linguists' claim that uniformation in language behavior exist in a given society at a given time. It was an attempt to ascertain if there are regularities in their linguistic behavior for these functions and to find out how these regularities are related to non-linguistic factors like age, status, sex and social situation.